Commodity-Choice Behavior with Pigeons as Subjects - Battalio, Raymond C.; Kagel, John H.; Rachlin, Howard; Green, Leonard (Journal of Political Economy, 1981)
Starting from an initial (baseline) budget line, income-compensated price changes always resulted in substitution effects consistent with the Slutsky-Hicks theory. This behavior cannot be explained by a simple random-behavior model. Similar changes in relative prices that did not originate from the initial (baseline) budget line resulted in "undersubstitution effects": The composition of consumption changed in the expected direction, but the magnitude of change was not large enough to be consistent with the initial commodity bundle chosen. These undersubstitution effects are not explainable by shifting preference patterns or anchoring effects found in inconsistent choice sequences with human subjects.